An Analysis of Students’ Perceptions in Implementation 2013 Curriculum on Senior High School English Language Teaching (ELT) in Bojonegoro - Mohammad Fatoni; Moh. Zainuddin (Jurnal Pendidikan Edutama, 2021)
Abstract: This study aims to analyze students’ perception in implementation of the 2013 curriculum on senior high school English language teaching (ELT) in Bojonegoro in (1) How are the students’ perceptions of the 2013 curriculum in terms of the learning process senior high school English language teaching?(2) How are the students' perceptions on the 2013 curriculum in terms of learning support in senior high school English language teaching?. Results of the analysis of students' perceptions of the 2013 curriculum in English Language Learning and Teaching in terms of the learning process and learning support, they were answered with a questionnaire. The learning process shows the following results: knowledge-perception (81%), exploration (84%), consolidation of learning (81%), the formation of attitudes and behavior (84%), formative assessment (81%), and learning support as follows: teacher quality (97%), student quality (90%) facility quality (68%). It can be concluded that the students' perceptions about the 2013 curriculum were positive, with the percentage strongly agreeing or very suitable between 76% -100%. Keywords: 2013 Curriculum; Students’ Perceptions; English Language Teaching (ELT); Qualitative Research Abstrak: Penelitian ini bertujuan untuk menganalisis persepsi siswa dalam implementasi kurikulum 2013 pada pengajaran bahasa Inggris di sekolah menengah atas (ELT) di Bojonegoro dalam (1) Bagaimana persepsi siswa terhadap kurikulum 2013 ditinjau dari proses pembelajaran pada pembelajaran bahasa Inggris di SMA? (2) Bagaimana persepsi siswa terhadap kurikulum 2013 dalam hal dukungan pembelajaran pada pembelajaran bahasa Inggris di SMA ?. Hasil analisis persepsi siswa terhadap kurikulum 2013 dalam Pembelajaran dan Pengajaran Bahasa Inggris ditinjau dari proses pembelajaran dan penunjang pembelajaran dijawab dengan angket. Proses pembelajaran menunjukkan hasil sebagai berikut: pengetahuan-persepsi (81%), eksplorasi (84%), konsolidasi pembelajaran (81%), pembentukan sikap dan perilaku (84%), penilaian formatif (81%) dan dukungan pembelajaran sebagai berikut: kualitas guru (97%), kualitas siswa (90%) kualitas fasilitas (68%). Dapat disimpulkan bahwa persepsi siswa terhadap kurikulum 2013 adalah positif dengan persentase sangat setuju atau sangat sesuai antara 76% -100%. Kata Kunci: Kurikulum 2013; Persepsi Siswa; Pengajaran Bahasa Inggris (ELT); Penelitian kualitatif